Interaksi Sosial Nabi Muhammad Saw dan Komunitas Yahudi: Telaah Hadis dalam Perspektif Historis-Psikologis - A’yun, Qurrota; Budiman, Arif (Tahdis: Jurnal Kajian Ilmu Al-Hadis, 2024)
This article aims to examine the relationship between the Prophet Muhammad and the Jewish community in Medina based on traditions, primarily from the book of Ṣaḥīḥ al-Bukhārī. The research focuses on the social interactions, both positive and negative, as well as the political, social and religious factors that influenced this relationship. Using a qualitative research design through analysis of hadith texts and Islamic historical literature, historical and psychological approaches were taken to analyze these interactions. This research resulted in the following findings: First, in general, it is found that there is a historical fact that there is a form of cooperation and respect between the Prophet and the Jews in two crucial cases, namely satire literature and the case of killing a Jewish person so that there is tension. Second, from the psychological context, the factor that causes conflict and confrontation is the factor of cultural inheritance (transferred culture) is a significant factor in influencing the Prophet’s relationship with the Jewish community. The negative disposition that has been rooted is proven to erupt various acts of treason in various forms.